Gold and colloidal gold surface influence on dna conformational change - Dovbeshko, G.I.; Gnatyuk, O.P.; Chegel, V.I.; Shirshov, Y.M.; Kosenkov, D.V.; Andreev, E.A.; Tajmir-Riahi, H.A.; Lytvyn, P.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
DNA conformational changes caused by gold and colloidal gold surface have been studied by surface enhanced infrared spectroscopy (SEIRA), spectroscopy of plasmon resonance (SPR), atomic force microscopy (AFM) and principal component analysis. Experimental data have shown that DNA conformation is slightly influenced by gold surface, while it is strongly altered by colloidal gold. Spectroscopic features of DNA-colloidal gold system have shown that the intensity of the asymmetric PO₂– band at 1240 cm⁻¹ decreases by two times, and that of symmetric band at 1090 cm⁻¹ decreases by 2.4 times whereas the halfwidth of phosphate bands increases by 35–40 cm⁻¹; a frequency shift of asymmetric band position from 1240 to 1246 cm⁻¹ and a symmetric band from 1090 to 1106 cm⁻¹ has been observed. It was shown that intensity variation and shift of DNA base vibrations together with the broadening of OH, NH, and CH stretching vibrations occur due to DNA conformational changes and the redistribution of the H-bonding network. A supposition about DNA condensation by colloidal gold was made. SEIRA and AFM data have showed major DNA structural changes occurred on gold colloidal particles. It was found that all the spectral features are more prominent for DNA–colloidal gold system deposited on gold substrate than on CaF₂ substrate.